LncRNA AFAP1-AS1 Supresses miR-139-5p and Promotes Cell Proliferation and Chemotherapy Resistance of Non-small Cell Lung Cancer by Competitively Upregulating RRM2 - Huang, Na; Guo, Wei; Ren, Ke; Li, Wancheng; Jiang, Yi; Sun, Jian; Dai, Wenjing; Zhao, Wei (Frontiers in Oncology, 2019)
Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related death worldwide. This study aims to understand the underlying mechanism of lncRNA, actin filament-associated protein 1 antisense RNA 1(AFAP1-AS1) in mediating chemotherapeutic resistance in NSCLC. The levels of AFAP1-AS1 in NSCLC tissues and cells were determined using RT- PCR. The protein levels of RRM2, EGFR and p-AKT were analysed using Western blotting. Binding between AFAP1-AS1 and miR-139-5p was confirmed using dual luciferase reporter and RNA immunoprecipitation (RIP) assays, and binding between miR-139-5p and RRM2 was confirmed by a dual luciferase reporter assay. NSCLC cell proliferation, apoptosis, and colony formation were examined using MTT, flow cytometry, and colony formation assays, respectively. It was found that AFAP1-AS1 expression was upregulated in NSCLC tissues and cells. In addition, AFAP1-AS1 bound to and downregulated the expression of miR-139-5p, which was reduced in NSCLC tissues. Knockdown of AFAP1-AS1 and overexpression of miR-139-5p inhibited NSCLC cell proliferation, colony formation and chemotherapy resistance and increased cell apoptosis. Additionally, AFAP1-AS1 upregulates RRM2 expression via sponging miR-139-5p. Furthermore, AFAP1-AS1 enhanced NSCLC cell proliferation and chemotherapy resistance through upregulating RRM2 by inhibiting miR-139-5p expression. Moreover, RRM2 promoted cellular chemotherapy resistance by activating EGFR/AKT. Finally, knockdown of AFAP1-AS1 significantly suppressed tumour growth and chemoresistance in nude mice. In conclusion, AFAP1-AS1 promoted chemotherapy resistance by supressing miR-139-5p expression and promoting RRM2/EGFR/AKT signalling pathway in NSCLC cells.